Specific Features and Problems of Development of the Modern Siberian Cities' Regional Art Market: Case Study of Krasnoyarsk City - Nemaeva, Natalia O.; Obmorokova, Anastasia M.; Khvastunov, Aleksei V. (International Journal of Economics and Financial Issues, 2016)
The art market of the Siberian regions is in its nascent stage and in search of its own identity, its own unique regional features capable of making art goods more competitive. Art salons and galleries as main art business centers play a very important role in adjusting the mechanisms of intra-institutional positive dynamics as they specify the way of development of the region's fine art, cooperate with leading artists, serve as a communication means between the artist and the consumer, and set prices in the art sphere. The purpose of this paper is to analyze the dynamics of development of Krasnoyarsk's art market in the context of development of the All-Russian fine art market, to identify its strengths and weaknesses, and to determine key factors that positively or negatively affect this market's competitiveness. The paper presents the whole situation in the country's art market and analyzes statistical data about Krasnoyarsk's art market. It shows existing conditions and characteristics that identify the regional art market's specific features and reveals main problems associated with this market's development. Methods used to study are analysis of economic statistics, study of marketing strategies of leading art galleries and salons, interviews with sellers, managers and potential buyers. The conclusions of this study can help to create a rational strategy for positive development of the Siberian cities' art market and can be used for identifying the prospects of development of the regional fine art market in the future. Keywords: art market, art dealer, marketing strategy, brand JEL Classifications: 19, M31, Z11